Corrigendum to “Viscosity of bubbly magmas from torsional experiments on pumice” [Journal of Volcanology and Geothermal Research 461 (2025) 108297] - Gaetano Ferrante; Helge Gonnermann; Céline Fliedner; Thomas Giachetti; Amy G. Ryan (Journal of Volcanology and Geothermal Research, 2025)

P18-20 Building Bridges in Tobacco Harm Reduction: A Global Interlaboratory Initiative for Standardized Smoke and Aerosol Exposure Assessment - M. Caruso; R. Emma; P. Zuccarello; S. Rust; G. Carota; K. Poulas; F. Zadjali; A. Sun; V. Volarevic; R. Lesmana; M. Tobi; K. Mesiakaris; et al. (Toxicology Letters, 2025)

Viscosity of bubbly magmas from torsional experiments on pumice - Gaetano Ferrante; Helge Gonnermann; Céline Fliedner; Thomas Giachetti; Amy G. Ryan (Journal of Volcanology and Geothermal Research, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

Experimental considerations support the use of artificial sentinel prey—a comment on Rodriguez‐Campbell et al - Marco Ferrante; Andy G. Howe; Gabor L. Lövei (Journal of Biogeography, 2024)

Radiocontamination level of mussels (M. Galloprovincialis) collected in italy from apulian coasts and assessed dose to population - G. Trotta; N. Bortone; V. Nardelli; O. Miedico; R. Damiano; M.A. Ferrante; M. Langianese; M. Nicolini; M. Iammarino (Regional Studies in Marine Science, 2024)

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

A novel morphological phenotype does not ensure reduced biotic resistance on an oceanic island - M. Ferrante; R. Nunes; L. Lamelas-López; G. L. Lövei; P. A. V. Borges (Biological Invasions, 2022)

Correction to: Sant’Imbenia (Alghero): further archaeometric evidence for an Iron Age market square - M. Clemenza; B. Billeci; M. Carpinelli; M. Ferrante; E. Fiorini; G. Gasperetti; S. Nisi; P. Oliva; V. Sipala; P. R. Trincherini; I. M. Villa; M. Rendeli (Archaeological and Anthropological Sciences, 2021)

Sant’Imbenia (Alghero): further archaeometric evidence for an Iron Age market square - M. Clemenza; B. Billeci; M. Carpinelli; M. Ferrante; E. Fiorini; G. Gasperetti; S. Nisi; P. Oliva; V. Sipala; P. R. Trincherini; I. M. Villa; M. Rendeli (Archaeological and Anthropological Sciences, 2021)
Lead isotope compositions were determined for 18 metal objects from the archaeological site of Sant’Imbenia, NW Sardinia, dating to the end of the ninth century BCE onwards. The provenance of some objects is unambiguously traced to SW Sardinia; other objects could derive either from central Sardinia or the Iberian coastal ranges. The variety of the provenances attests to a wide trade network that spanned the entire island of Sardinia and extended to the Iberian sites.

Lead isotope evidence of lead supply in ancient Ilduro (second-first centuries B.C.E.) - Alejandro G. Sinner; Marco Ferrante; Stefano Nisi; Pier Renato Trincherini (Archaeological and Anthropological Sciences, 2020)

Habitat change and alteration of plant and invertebrate communities in waterbodies dominated by the invasive alien macrophyte Lemna minuta Kunth - S. Ceschin; G. Ferrante; F. Mariani; L. Traversetti; N. T. W. Ellwood (Biological Invasions, 2020)

Biotic and Abiotic Drivers of Topsoil Organic Carbon Concentration in Drylands Have Similar Effects at Regional and Global Scales - Juan J. Gaitán; Fernando T. Maestre; Donaldo E. Bran; Gustavo G. Buono; Andrew J. Dougill; Guillermo García Martínez; Daniela Ferrante; Reginald T. Guuroh; Anja Linstädter; Virginia Massara; Andrew D. Thomas; Gabriel E. Oliva (Ecosystems, 2019)

Genome editing in diatoms: achievements and goals - Peter G. Kroth; Atle M. Bones; Fayza Daboussi; Maria I. Ferrante; Marianne Jaubert; Misha Kolot; Marianne Nymark; Carolina Río Bártulos; Andrés Ritter; Monia T. Russo; Manuel Serif; Per Winge; et al. (Plant Cell Reports, 2018)

Ground-level predation on artificial caterpillars indicates no enemy-free time for lepidopteran larvae - M. Ferrante; G. Barone; M. Kiss; E. Bozóné-Borbáth; G. L. Lövei (Community Ecology, 2017)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Effects of Pseudomonas fluorescens Seed Bioinoculation on Heavy Metal Accumulation for Mirabilis jalapa Phytoextraction in Smelter-Contaminated Soil - M. Petriccione; D. Di Patre; P. Ferrante; S. Papa; G. Bartoli; A. Fioretto; M. Scortichini (Water, Air, & Soil Pollution, 2013)

Cadmium Accumulation and Antioxidant Responses in Sparus aurata Exposed to Waterborne Cadmium - T. Cirillo; R. Amodio Cocchieri; E. Fasano; A. Lucisano; S. Tafuri; M. C. Ferrante; E. Carpenè; G. Andreani; G. Isani (Archives of Environmental Contamination and Toxicology, 2012)

CNTO 95, a fully human anti αv integrin antibody, inhibits cell signaling, migration, invasion, and spontaneous metastasis of human breast cancer cells - Qiming Chen; Carol D. Manning; Hillary Millar; Francis L. McCabe; Catherine Ferrante; Celia Sharp; Lillian Shahied-Arruda; Parul Doshi; Marian T. Nakada; G. Mark Anderson (Clinical & Experimental Metastasis, 2008)

Rapid degradation of articular cartilage proteoglycan by neutrophils: Comparison with macrophages and synovial fibroblasts - D.A. Halliday; G. Clemente; D.A. Rathjen; A. Ferrante (Inflammation Research, 2000)

Subgrouping of human rotavirus strains by complement fixation, indirect double-antibody sandwich enzyme-linked immunosorbent assay and solid-phase immune electron microscopy - G. Gerna; M. Torsellini; N. Passarani; M. Battaglia; E. Percivalle; A. Sarasini; D. Torre; P. Ferrante (Archives of Virology, 1984)